Antidotes and Counter-Poisons in the Ancient World: Onions (hdw) (Allium cepa L.) in Egypt, the Preferred Antitoxic for Snake Bites - Rosso, Ana María.
Modern toxicology focuses on studying adverse effects of poisons and chemical exposures but understanding the toxicity and risks developing antidotes and counter-poisons has taken science a long time. The lack of a proper theory in antiquity to treat poisoned patients didn’t allow for the improvement in diagnosis and treatment. However, in Papyrus Brooklyn 47.2180 dated to the fourth century bc, ancient Egyptians classified local snakes, poisonous symptoms, diagnosis, and simple treatments with drugs and magical incantations, ignoring the effectiveness of remedies and their potential side effects. To solve the problem and protect themselves, people first tried to observe animal behavior and the reactions to different substances ingested. Ancient medicine found certain alexipharmic therapy or antidotes to reverse lethal intoxication based on two axioms: similia similibus, studying the tolerance of a poison and the dose, as with the modern theory of immunity, and contraria contraris, using substances with contrary properties, as in the case of antibiotics. This allowed the development of pharmacology, because “For the Egyptians, poisons are substances that may be offset by antidotes or substances with opposite properties.” An extremely common food, the Egyptian species of onion Allium cepa L., seemed to be the preferred alexipharmic to repel snake venom. Its characteristic smell comes from a volatile and fragrant sulphide gas and, through recent chemical research, scientists have reported its antibiotic properties, since it contains allium, transformed in allicin, the key ingredient responsible for its broad-spectrum and anti-bacterial activity. Useful for all kinds of treatment in the Egyptian pharmacopoeia, its defensive power also became known abroad. http://dx.doi.org/10.5913/jarce.55.2019.a011